An Exploration of Sensation Seeking in Persons With Disabilities in Rehabilitation. Issue 4 (July 2019) - Koszalinski, Rebecca S.; Heidel, R. Eric; Thomson, Cynthia J.; Cochran, P. David; Nance, Jon; Kaye, Al
Abstract: Purpose: This study reports the findings of a study about sensation-seeking or high-risk/challenging sports in persons who have disabilities. Design: Exploratory, cross-sectional, and descriptive. Methods: Two hundred and twenty-three recruitment e-mails were sent to potential participants. Data were collected through Qualtrics. Findings: Mean score for Contextual Sensation Seeking Questionnaire for Skiing and Snowboarding ( M = 30.21, SD = 8.18) was significantly lower than a sample of able-bodied skiers and snowboarders, t(239) = 2.75, p = .006. Mean for impulsive sensation seeking was lower than the same sample of able-bodied athletes cited in a previous study, t (240) = 4.56, p = .001. Means for the Zuckerman Kuhlman Personality Questionnaire subscales were impulsivity ( M = 1.98, SD = 4.05) and sensation seeking ( M = 6.75, SD = 2.68). Conclusions: This group scored lower in sensation seeking compared to able-bodied high-risk/challenging sports activities participants. Sensation seeking is not a motivating factor in this sample. Clinical Relevance: Nurses could encourage rehabilitation patients to engage in challenging activities for personal and group mastery.